2020
DOI: 10.1016/j.tcr.2020.100351
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-aneurysm of the lateral circumflex femoral artery after femoral neck fracture – A case report

Abstract: Only one case of injury of the lateral circumflex femoral artery secondary to a femoral neck fracture has been reported. We present a second case of this rare injury. A 59-year-old gentleman fell from an embankment, from approximately two meters in height, while landscaping and landed onto his left side. He suffered immediate pain in his left hip and was unable to weight bear. X-ray demonstrated a Garden II left femoral neck fracture. Within 24 of the injury, he underwent percutaneous internal fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The literature review revealed only five cases with vascular injury of the lateral circumflex femoral artery. Four of them concern pseudoaneurysm formation after fixation of femoral neck fracture [ 8 - 11 ] and only one concerns an intertrochanteric fracture [ 12 ]. Vascular injury in the cases with femoral neck fracture was caused after the fracture fixation due to iatrogenic intervention, while in the intertrochanteric fracture case, the injury of the lateral circumflex femoral artery was caused by the lesser trochanter fragment.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review revealed only five cases with vascular injury of the lateral circumflex femoral artery. Four of them concern pseudoaneurysm formation after fixation of femoral neck fracture [ 8 - 11 ] and only one concerns an intertrochanteric fracture [ 12 ]. Vascular injury in the cases with femoral neck fracture was caused after the fracture fixation due to iatrogenic intervention, while in the intertrochanteric fracture case, the injury of the lateral circumflex femoral artery was caused by the lesser trochanter fragment.…”
Section: Discussionmentioning
confidence: 99%